The Implementation of Text-Based Approach within the Competency-Based Curriculum in Junior High School - Desta, Mutiara; Nanda, Rizka; Herlinda, Silvi; Hasibuan, Kalayo (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This article discusses the implementation of the Text-Based Approach (TBA) within the Competency-Based Curriculum (CBC) in junior high schools. The TBA aims to enable learners to communicate orally and written in target language (English). The CBC, on the other hand, focuses on mastery of skills and knowledge, allowing learners to progress at their own pace. The integration of these two approaches is crucial for effective teaching and learning outcomes. This article highlights the importance of understanding the principles of CBC and TBA to enhance educational tactics and improve learning outcomes.